1991
DOI: 10.3989/gya.1991.v42.i1.1275
|View full text |Cite
|
Sign up to set email alerts
|

Absorción de grasas termoxidadas. I. Reproducibilidad y exactitud de las técnicas analíticas previas a la evaluación de los lípidos no absorbidos

Abstract: Absorption of thermoxidízed fats. I. Reproducibility and accuracy of the previous analytical techniques used for the evaluation of non-absorbed lipids.Reproducibility of the techniques used for isolation and separation of non-absorbed lipids present in feces from rats fed with diets containing heated oils are defined.Highly reproducible results have been found for total lipids, nonpolar fatty acid compositions. Results obtaines from extracted diets demonstrate both the absence of significant alteration and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…triacylglycerol dimers and polymers, are not readily hydrolyzed, as shown by in vitro enzymatic hydrolysis studies on thermally oxidized and used frying oils and fats (Arroyo et al 1996;Márquez-Ruiz et al 1992aSánchez-Muniz et al 2000). Moreover, deficiencies in dimers and polymers hydrolysis were found to affect signifi cantly the release and hence digestibility of oxidized monomeric and even unoxidized fatty acids (Márquez-Ruiz et al 1991;1992a, 1992b, 1992cMárquez-Ruiz and Dobarganes, 1995;Sánchez-Muniz et al 1999;González-Muñoz et al 2003). Impairment of polymeric triacylglycerol hydrolysis and the subsequent effect on cholesterol micellar solubilization could explain that excretion of endogenous sterols, particularly cholesterol, was markedly higher in rats fed diets containing thermoxidized oils versus nonheated oils .…”
Section: Enzymatic Hydrolysis and Absorption Of Oxidized Dietary Lipidsmentioning
confidence: 99%
“…triacylglycerol dimers and polymers, are not readily hydrolyzed, as shown by in vitro enzymatic hydrolysis studies on thermally oxidized and used frying oils and fats (Arroyo et al 1996;Márquez-Ruiz et al 1992aSánchez-Muniz et al 2000). Moreover, deficiencies in dimers and polymers hydrolysis were found to affect signifi cantly the release and hence digestibility of oxidized monomeric and even unoxidized fatty acids (Márquez-Ruiz et al 1991;1992a, 1992b, 1992cMárquez-Ruiz and Dobarganes, 1995;Sánchez-Muniz et al 1999;González-Muñoz et al 2003). Impairment of polymeric triacylglycerol hydrolysis and the subsequent effect on cholesterol micellar solubilization could explain that excretion of endogenous sterols, particularly cholesterol, was markedly higher in rats fed diets containing thermoxidized oils versus nonheated oils .…”
Section: Enzymatic Hydrolysis and Absorption Of Oxidized Dietary Lipidsmentioning
confidence: 99%
“…In the light of such results, the objective of the present study was to compare the in vitro versus in vivo hydro lytic action on thermally oxidized oils as well as to differentiate hydrolysis/absorption con tribution to the low digestibility coefficients found in heat-oxidized oils [16].…”
Section: Introductionmentioning
confidence: 99%
“…(2) comparison between free fatty acids and total fatty acids in faecal lipids through acidity values, before and after chemical hy drolysis of the samples; the level of esterified fatty acids, calculated by difference, is an indicator of those fatty acyls which remain non-hydrolyzed; (3) quantitation of non-absorbed free and esterified levels of two specific groups of com pounds present in heated oils -non-altered fatty acids and non-polar dimer fatty acids; our previous nutritional studies on thermally oxidized oils indicated unexpected digestibil ity values for both groups of compounds [16].…”
Section: Introductionmentioning
confidence: 99%
“…Posteriormente, se llevó a cabo la extracción de los lípidos neutros mediante Soxhiet, utilizando éter etílico como disolvente (Márquez-Ruiz et al, 1991). Con objeto de garantizar la total extracción de los lípidos, las heces ya extraídas se someten a hidrólisis en frío con CIH 3N y se extraen nuevamente con éter etílico mediante Soxhiet.…”
Section: Extracción De Lípidos No Absorbidosunclassified